Deconstructing esports - Tom Legierse; Maria Ruotsalainen (Eludamos)
Branding competitive gaming as esports, part of a process known as sportification, has contributed greatly to the wider acceptance of competitive gaming as legitimate leisure and professional activity. However, the social effects of sportification remain largely overlooked in current research. In this paper we argue that in order to understand the normative and formative social effects of sportification of competitive gaming, we need to forefront the bodies in esports. Building on scholarship that highlights inequities in (competitive) gaming and esports, we identify four ways in which bodies are made relevant in esports: 1) the obscuring of the playing body and establishment of an idealized and normative masculine athletic body; 2) the ‘visibility’ of women's bodies as deviant from the norm; 3) the invisibility (and impossibility) of disabled bodies through design (embodied nature of design of both games and gameplay); and 4) the embodied nature of infrastructural issues that cannot be reduced to materiality. We argue for a deconstruction of esports as a social practice that forefronts bodies. Understanding exactly how bodies become relevant will allow us to deconstruct the structural conditions of participation that dictate which bodies are possible or not in esports and move towards more equitable esports practices.